Juridical Review of the Implementation of the Self Assessment System in Tax Collection in Indonesia - R. Narendra Jatna; Hasbullah Hasbullah; Abdul Kadir Jaelani (Audito Comparative Law Journal (ACLJ), 2026)
The self-assessment system is a key pillar of global tax reform that gives taxpayers full confidence to calculate, pay, and report their taxes independently. Although this trust-based system has been implemented in Indonesia since 1983, previous legal studies have been trapped in normative analysis of regulations and often ignore the asymmetry of empirical compliance and the dynamics of administrative digitalisation in mitigating the moral hazard of taxpayers. This study aims to comprehensively examine the legal basis for the implementation of the self-assessment system in Indonesia and analyse the structural obstacles and tactical efforts of the government in optimising taxpayers' legal compliance through a juridical-normative approach. The findings of the study show that normatively, the available legal framework has been aligned with the principles of legal certainty and accountability; however, its effectiveness is empirically hampered by low tax literacy and limited supervision. The novelty of this research proves that the integration of the modernisation of tax technology (digitalisation) and strengthening of administrative law enforcement is the most crucial hybrid instrument to close the loopholes of the weaknesses of the conventional system. Theoretically, the study enriches the tax law literature on the concept of voluntary compliance in the digital age, while practically providing concrete recommendations for fiscal authorities in designing responsive supervisory policies and risk-segmentation-based education programs